Estimating the Impact of Remote Work Policies on Productivity and Improving Welfare in Developing Countries: A Case Study of Indonesia - Ade Fitria Fatimah (Sekolah Tinggi Agama Islam Kuningan, 2025)
The global COVID-19 pandemic has accelerated the adoption of remote work policies in various countries, including developing countries such as Indonesia. This policy has a significant impact on labor productivity patterns and worker welfare, especially in sectors that can adapt to digital technology. However, the long-term impact of remote work on productivity and well-being in developing countries is still a debate that requires empirical evidence. This study aims to estimate the impact of remote work policies on labor productivity and welfare improvement in Indonesia. This study uses econometric methods with panel data analysis from the national labor force survey and relevant secondary data, incorporating a fixed-effects model to control for unobserved variables that may affect worker productivity and welfare. Data was collected from several key economic sectors during the period before and after the widespread adoption of remote work. The results of the study show that remote work policies have a significant positive impact on productivity in the information and communication technology sector, while the traditional sector shows mixed results. The improvement in worker welfare was recorded mainly in the aspect of work-life balance, as well as the reduction of travel time and costs. These findings highlight the importance of policies that support digital infrastructure and skills development to optimize the benefits of remote work in Indonesia.